A Novel Pineal Night-Specific ATPase Encoded by the Wilson Disease Gene - Borjigin, Jimo (J Neurosci, 1999)
We have identified a pineal night-specific ATPase (PINA), a novel splice variant of the ATP7B gene disrupted in Wilson disease (WD). PINA expression exhibits a dramatic diurnal rhythm in both pineal gland and retina with 100-fold greater expression at night than at day. PINA is expressed in pinealocytes and a subset of photoreceptors in adult rats and is transiently expressed in the retinal pigment epithelium and the ciliary body during retinal development. Nocturnal pineal expression of PINA is under the control of a suprachiasmatic nucleus clock mediated by superior cervical ganglion innervation of the pineal. In vitro, PINA expression in pineal cells can be stimulated by agents activating the cAMP signal transduction pathway. PINA is able to restore copper transport activity in Saccharomyces cerevisiae deficient in the homologous copper-transporting ATPase CCC2, suggesting that this protein may function as a copper transporter in rat pinealocytes. These studies suggest a potential role of rhythmic copper metabolism in pineal and/or retina circadian function.